Efficacy and safety of traditional Chinese medicine for intracranial hemorrhage by promoting blood circulation and removing blood stasis: A systematic review and meta-analysis of randomized controlled trials - Lin, Wenjian; Hou, Jingjing; Han, Tianxiong; Zheng, Li; Liang, Huazheng; Zhou, Xiaoyu (Frontiers in Pharmacology, 2022)
Background: Although blood-activating Chinese medicine (BACM) has been reported as adjuvant therapy for intracranial hemorrhage (ICH) in China, high-quality evidence is still lacking. Our study aimed to collect the latest high-quality randomized controlled trials (RCTs) and to evaluate the efficacy and safety of BACM for ICH. Methods: RCTs published between January 2015 and March 2022 were searched in databases, including China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Sino-Med, Wanfang, PubMed, Web of Science, Cochrane Library, and Embase without language restrictions. Eligible RCTs were included and both primary (clinical efficacy evidenced by decreased neurological deficit scores) and secondary outcomes (increased Barthel index, decreased NIHSS, hematoma volume, the volume of cerebral edema, the incidence of side effects, and mortality) were analyzed. The quality of included RCTs was assessed using the Cochrane risk of bias tool. In the meta-analysis, the pooled results were analyzed using Review Manager 5.3 and STATA14.0. Finally, The GRADEpro GDT software (Guideline Development Tool) was used to summarize the results. Sensitivity and subgroup analyses were conducted based on the follow-up time. Results: Fifteen RCTs, involving 1,579 participants, were included for analysis in our study. The pooled outcomes indicated that BACM combined with western medicine treatment (WMT) was superior to WMT alone for patients with ICH, demonstrated by the improvements in efficacy (RR = 1.22 (95% CI, [1.13 to 1.32], p < 0.001), neurological functions (MDNIHSS = −2.75, 95% CI [−3.74 to −1.76], p < 0.001), and activities of daily living (MDBarthel index = 5.95, 95% CI [3.92 to 7.98], p < 0.001), as well as decreased cerebral hematoma, cerebral edema (MD cerebral hematoma = −2.94, 95% CI [−3.50 to −2.37, p < 0.001 and MDcerebral edema = −2.66, 95% CI [−2.95 to −2.37], p < 0.001), side effects and mortality (RR = 0.84 (95% CI [0.60 to 1.19], p = 0.330 and RR = 0.51 (95% CI, [0.16 to 1.65], p = 0.260). In addition, Conioselinum anthriscoides “Chuanxiong” [Apiaceae], Camellia reticulata Lindl. [Theaceae], and Bupleurum sibiricum var. jeholense (Nakai) C.D.Chu [Apiaceae]) were the most frequently used herbs in the treatment of ICH. Recently, there was a trend toward the extensive use of another two herbs, including Rheum palmatum L. [Polygonaceae], Astragalus mongholicus Bunge [Fabaceae]) for ICH. Conclusion: BACM combined with WMT seems to be superior to WMT alone for patients with ICH. Further high-quality RCTs are warranted to confirm the efficacy and safety of BACM.